A Strategy for Nurturing Growth: Building Competitive Advantage Through Personalized Care in A Crowded Market - Damanik, Jordy Roy Armando; Prabandari, Sri Palupi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to formulate a competitive strategy for RSU Yoshua, a private Type C hospital, to improve its market position, enhance service quality, and support long-term sustainability amid increasing competition in the healthcare industry. Design/Methodology/Approach – This study employs a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews, internal documents, and literature reviews using data triangulation. Strategic analysis was conducted using the Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, SWOT analysis, Internal-External (IE) Matrix, and Quantitative Strategic Planning Matrix (QSPM). Findings – The results indicate that RSU Yoshua is positioned in a “hold and maintain” strategic position, reflecting moderate internal capabilities within a relatively favorable external environment. The QSPM analysis identifies three priority strategies: utilizing experienced teams to provide personalized services and improve patient satisfaction, investing in digital marketing to increase market visibility, and optimizing the hospital’s strategic location through telehealth services and community outreach programs. Originality/Value: This study offers value by applying the David and David strategic management model to a resource-limited private hospital context, demonstrating its practical relevance for smaller healthcare institutions. The integration of digital transformation, patient-centered service innovation, and geographically driven outreach creates a novel strategic framework that can guide similar hospitals in enhancing competitiveness and long-term sustainability.